Aspergillus oryzae NRRL 35191 from coffee, a non-toxigenic endophyte with the ability to synthesize kojic acid (2012)
Aspergillus oryzae NRRL 35191 was isolated as an endophyte from coffee leaves and found to produce kojic acid (KA) in culture. When inoculated into cacao seedlings (Theobroma cacao), A. oryzae grew endophytically and synthesized KA in planta. Cacao seedlings inoculated with A. oryzae produced higher levels of caffeine than non- inoculated ones. Aspergillus oryzae may be a useful endophyte to introduce to cacao since it grows non- pathogenically and induces the caffeine defense response that may make the plant more tolerant to insects and pathogens.